The - Blau, Joel (Oxford University Press, 2004)
The Dynamics of Social Welfare Policy reinvents the contemporary social welfare policy textbook. Organized around the explicit premise that every kind of social work practice embodies a social welfare policy, the book develops three types of knowledge: (1) a description of social welfare policy, (2) a model for understanding any social welfare policy, and (3) tools for thinking critically about social welfare. Recognizing the fluidity of social welfare, the book also helps undergraduate and graduate students identify the triggers that lead to changes in social policy, and, in turn, influence what social workers actually do...